A re-examination of the reaction of dichloro-tris-(triphenylphosphino)ruthenium(II) with benzonitrile: Crystal structures of triphenylphosphine chloro ruthenium complexes. (16th August 2016) - Cruz, Santina S.; Amenta, Donna S.; Gilje, John W.; Yap, Glenn P.A.
Graphical abstract: The reaction of RuCl2 (PPh3 )3 with excess benzonitrile yields cis -RuCl2 (PPh3 )2 (NCPh)2, whereas (PPh3 )2 (Cl)Ru(μ-Cl)3 Ru(NCPh)(PPh3 )2 is obtained with excess RuCl2 (PPh3 )3 . Abstract: The reaction of RuCl2 (PPh3 )3 with benzonitrile has been investigated in toluene. When excess benzonitrile is employed cis -RuCl2 (PPh3 )2 (NCPh)2 is obtained and has been characterized by X-ray diffraction. This contrasts to acetonitrile which yields trans -RuCl2 (PPh3 )2 (NCMe)2 . With excess RuCl2 (PPh3 )3 a triply chloro bridged diruthenium compound (PPh3 )2 (Cl)Ru(μ-Cl)3 Ru(NCPh)(PPh3 )2 is obtained. A dark red crystalline side product, formed during the preparation of RuCl2 (PPh3 )3, is identified as [Ph3 PMe][RuCl4 (PPh3 )2 ] by low temperature crystal structure determination with better precision than previously reported. In each case, the Ru atom presents octahedral coordination geometry.